Outcomes in anticoagulated patients with atrial fibrillation and with mitral or aortic valve disease - Vinereanu, Dragos; Wang, Alice; Mulder, Hillary; Lopes, Renato D; Jansky, Petr; Lewis, Basil S; Gersh, Bernard J; Avezum, Alvaro; Hanna, Michael; Held, Claes; Wallentin, Lars; Granger, Christopher B; et al. (Heart (British Cardiac Society), 2018)
OBJECTIVE: To assess stroke/systemic embolism, major bleeding and other outcomes, and treatment effect of apixaban versus warfarin, in patients with atrial fibrillation (AF) and different types of valvular heart disease (VHD), using data from the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation trial. METHODS: There were 14 793 patients with known VHD status, categorised as having moderate or severe mitral regurgitation (MR) (n=3382), aortic regurgitation (AR) (n=842) or aortic stenosis (AS) (n=324); patients with moderate or severe mitral stenosis were excluded from the trial. Baseline characteristics, efficacy and safety outcomes were compared between each type and no significant VHD. Treatment effect was assessed using an adjusted model. RESULTS: Patients with MR or AR had similar rates of stroke/systemic embolism and bleeding compared with patients without MR or AR, respectively. Patients with AS had significantly higher event rates (presented as rate per 100 patient-years of follow-up) of stroke/systemic embolism (3.47 vs 1.36; adjusted HR (adjHR) 2.21, 95% CI 1.35 to 3.63), death (8.30 vs 3.53; adjHR 1.92, 95% CI 1.41 to 2.61), major bleeding (5.31 vs 2.53; adjHR 1.80, 95% CI 1.19 to 2.75) and intracranial bleeding (1.29 vs 0.51; adjHR 2.54, 95% CI 1.08 to 5.96) than patients without AS. The superiority of apixaban over warfarin on stroke/systemic embolism was similar in patients with versus without MR (HR 0.69, 95% CI 0.46 to 1.04 vs HR 0.79, 95% CI 0.63 to 1.00; interaction P value 0.52), with versus without AR (HR 0.57, 95% CI 0.27 to 1.20 vs HR 0.78, 95% CI 0.63 to 0.96; interaction P value 0.52), and with versus without AS (HR 0.44, 95% CI 0.17 to 1.13 vs HR 0.79, 95% CI 0.64 to 0.97; interaction P value 0.19). For each of the primary and secondary efficacy and safety outcomes, there was no evidence of a different effect of apixaban over warfarin in patients with any VHD subcategory. CONCLUSIONS: In anticoagulated patients with AF, AS is associated with a higher risk of stroke/systemic embolism, bleeding and death. The efficacy and safety benefits of apixaban compared with warfarin were consistent, regardless of presence of MR, AR or AS. CLINICAL TRIAL REGISTRATION: ARISTOTLE clinical trial number NCT00412984.
Keywords: pyrazoly; Humans; atrial fibrillation; mitral regurgitation; lidé středního věku; warfarin; aortic stenosis; mitrální chlopeň; Warfarin; Stroke; Pyridones; nemoci srdečních chlopní; Female; Aged; výsledek terapie; senioři; lidé; Atrial Fibrillation; Heart Valve Diseases; aortic regurgitation; Mitral Valve; cévní mozková příhoda; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Aged, 80 and over; pyridony; senioři nad 80 let; mužské pohlaví; Pyrazoles; aortální chlopeň; antikoagulancia; Anticoagulants; valvular heart disease; fibrilace síní; Aortic Valve